ANALISIS FAKTOR YANG MEMPENGARUHI PERUBAHAN LABA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Natalia, Erni Yanti (Universitas Merdeka Pasuruan, 2017)
The purpose of this research is to determine factors of changes profit in banking companies at Bursa Efek Indonesia (BEI). Independent variable that will be searched which are limited for NPL, ROA and BOPO variable. The populations of this research are all of the banking companies at BEI are private and foreign banking, there are 19 banking companies. The sampling method’s research is purposive sampling. The model research usage in this research is Doubled Regression Analysis. Data were analyzed by the Statistical Package for Social Science (SPSS) version 21, with a significance level (level sig) as 5% (0,05). The results of the research is showed some result finding, there are: (1) partially, the NPL has a positive impact and no significant effect on the change of profit (t count < t table with score 0.394 < t table 1,994 and significant score 0,695 > 0,05), 2) partially, the ROA has a negative impact and no significant effect on the change of profit (t count < t table with score -0.215 < t table 1,994 and significant score 0,830 > 0,05), 3) partially, the BOPO has a positive impact and no significant effect on the change of profit (t count < t table with score 0.276 < t table 1,994 and significant score 0,784 > 0,05). While simultaneously, NPL, ROA, and BOPO has a impact and no significant effect on the change of profit (F count < F table with score F count 0,142 < F table 2,732 and significant score 0,935 > 0,05).Keywords: NPL, ROA, BOPO, change of profit